Inhibition of mitochondrial cyclophilin D, a downstream target of glycogen synthase kinase 3α, improves sperm motility - Seung Hyun Park; Myung Chan Gye (BMC, 2024)
Abstract Background Cyclophilin D (CypD) negatively regulates ATP production by opening of the mitochondrial permeability transition pore. This study aimed to understand the role of CypD in sperm motility regulation. Methods Changes in CypD during sperm capacitation and its interaction with glycogen synthase kinase 3α (GSK3α), a key kinase regulating sperm motility, were examined in mouse spermatozoa. The effects of CypD inhibitor cyclosporin A (CsA) and GSK3 inhibitor 6-bromo-indirubin-3'-oxime (BIO) on sperm motility, p-GSK3α(Ser21), mitochondrial permeability transition pore (mPTP), mitochondrial membrane potential (MMP), and ATP production were examined. The effect of proteasome inhibitor MG115 on the cellular levels of CypD was examined. Results In cauda epididymal spermatozoa, GSK3α was found in both cytosolic and mitochondrial fractions whereas CypD was primarily found in the mitochondrial fraction together with ATP synthase F1 subunit alpha (ATP5A), a mitochondrial marker. GSK3α and CypD were co-localized in the sperm midpiece. Interaction between GSK3α and CypD was identified in co-immunoprecipitation. CsA, a CypD inhibitor, significantly increased sperm motility, tyrosine phosphorylation, mPTP closing, MMP, and ATP levels in spermatozoa, suggesting that CypD acts as a negative regulator of sperm function. Under capacitation condition, both GSK3α and CypD were decreased in spermatozoa but ATP5A was not. The GSK3 inhibitor BIO markedly increased p-GSK3α(Ser21) and decreased CypD but significantly increased mPTP closing, MMP, ATP production, and motility of spermatozoa. This suggests that inhibitory phosphorylation of GSK3α is coupled with degradation of CypD, potentiating the mitochondrial function. Degradation of CypD was attenuated by MG115, indicative of involvement of the ubiquitin proteasome system. Conclusions During sperm capacitation, CypD act as a downstream target of GSK3α can be degraded via the ubiquitin proteasome system, stimulating mitochondrial function and sperm motility.